Assessment of the risk of fracture in patients with gastrointestinal disease. - Arden, N; Cooper, C (2003)
Osteoporotic fractures are a common problem and associated with significant morbidity, mortality and costs. There is now increasing evidence that patients with coeliac disease are at an increased risk of osteoporotic fracture. With the advent of new therapeutic agents to reduce the risk of fracture, it is important to identify people at highest risk. The best predictors of future fracture include a previous osteoporotic fracture, low bone density, active inflammatory bowel disease, the use of oral corticosteroids and an increased risk of falling.